2010
DOI: 10.1007/s12043-010-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and comparison of vibrational and thermal properties of semi-organic nonlinear optical materials

Abstract: Single crystals of urea thiourea mercuric sulphate (UTHS) and urea thiourea mercuric chloride (UTHC), semi-organic nonlinear optical materials, were grown by lowtemperature solution growth technique by slow evaporation method using water as the solvent. Good quality single crystals were grown within three weeks. The nonlinear nature of the crystals was confirmed by SHG test. The UV-Vis spectrum showed the transmitting ability of the crystals in the entire visible region. FTIR spectrum was recorded and vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…During the course of a literature survey of metal compounds containing both thiourea and urea ligands, the title paper by Gunasekaran et al [1] reporting on growth of so called urea thiourea mercuric chloride (UTHC) and urea thiourea mercuric sulphate (UTHS) crystals attracted our attention. For formulating these crystals, the authors did not take into consideration the known chemistry of Hg(II) towards thiourea [2]; instead assumed that the mixing of urea, thiourea and mercuric chloride (or sulphate) in water will result in the formation of the so called UTHC (or UTHS) crystals by slow evaporation method.…”
mentioning
confidence: 99%
“…During the course of a literature survey of metal compounds containing both thiourea and urea ligands, the title paper by Gunasekaran et al [1] reporting on growth of so called urea thiourea mercuric chloride (UTHC) and urea thiourea mercuric sulphate (UTHS) crystals attracted our attention. For formulating these crystals, the authors did not take into consideration the known chemistry of Hg(II) towards thiourea [2]; instead assumed that the mixing of urea, thiourea and mercuric chloride (or sulphate) in water will result in the formation of the so called UTHC (or UTHS) crystals by slow evaporation method.…”
mentioning
confidence: 99%
“…Its UV-Vis spectra showed that the crystals had a wide optical window, no absorbance and good optical transmittance in the entire visible region. The FTIR analysis confirms the presence of functional groups in the grown crystals [3].The research related with amino acid single crystal like glycine with zinc chloride having good application in the field of NLO. [4] A Single crystal of L-Glycine was grown from aqueous solution by slow evaporation method.…”
Section: Introductionmentioning
confidence: 64%
“…The broad envelope in the high energy region between 3100cm -1 and 2600 cm -1 occurs in FT-IT spectrum indicates that, there is NH 3 + stretching vibrations presented in the sample and also the region of absorption bands extends to about 2000cm -1 due to multiple combination and overtone bands. The FT-IR spectrum of Tri-Glycine potassium chloride sample having spectral strong band between 3105cm -1 and 2608 cm -1 .…”
Section: Nh3 + Stretching Vibrationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Being the semiorganic materials they combine the advantages of the organics namely, higher polarizability and molecular engineering feasibility with that of inorganics namely, robustness and thermal stability. Organometallic complexes are formed by a combination of inorganic distorted polyhedron and asymmetrically conjugated organic molecular radicals [1,2].…”
Section: Introductionmentioning
confidence: 99%